2010
DOI: 10.1080/10934529.2010.500942
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to low-level heavy metals during pregnancy and birth size

Abstract: We evaluated the effect of environmental, low-level exposure to heavy metals during pregnancy, as estimated by urine analysis, on birth size of the newborns. Spot urine samples were collected from unexposed 78 pregnant women in Tokyo during 2007 and 2008. The urinary concentrations of beryllium (Be), copper (Cu), arsenic (As), zinc (Zn), selenium (Se), molybdenum (Mo), cadmium (Cd), tin (Sn), antimony (Sb), and lead (Pb) were measured by ICP-MS. The birthweight (BW), length (BL) and head circumference (HC) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
68
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 29 publications
9
68
5
Order By: Relevance
“…The observed urinary Cd in our study population was comparable with the pregnant women in Europe (median, 0.31 μg/L) (Akesson et al, 2002), and in the Pacific Northwest (median, 0.50-0.60 μg/g creatinine) (Mohanty et al, 2015). However, the Cd level in the present study was lower than that observed in pregnant women in Bangladesh (median, 0.64 μg/L) (Kippler et al, 2012) and in Japan (geometric mean, 0.77 μg/g creatinine; arithmetic mean, 0.98 μg/g creatinine) (Shirai et al, 2010).…”
Section: Discussioncontrasting
confidence: 85%
“…The observed urinary Cd in our study population was comparable with the pregnant women in Europe (median, 0.31 μg/L) (Akesson et al, 2002), and in the Pacific Northwest (median, 0.50-0.60 μg/g creatinine) (Mohanty et al, 2015). However, the Cd level in the present study was lower than that observed in pregnant women in Bangladesh (median, 0.64 μg/L) (Kippler et al, 2012) and in Japan (geometric mean, 0.77 μg/g creatinine; arithmetic mean, 0.98 μg/g creatinine) (Shirai et al, 2010).…”
Section: Discussioncontrasting
confidence: 85%
“…Multiple studies have found an association with SGA Odland et al, 1999;Xie et al, 2013;Gundacker et al, 2010;Jelliffe-Pawlowski et al, 2006;Berkowitz et al, 2006;González-Cossío et al, 1997) while others report no relationship (Shirai et al, 2010;Jones et al, 2010;Sowers et al, 2002). The different matrices used and the varying exposure levels may explain the conflicting results.…”
Section: Discussionmentioning
confidence: 74%
“…Several small studies have reported an association between urinary arsenic (primarily inorganic) and birthweight, including a study in Bangladesh (Rahman et al, 2009), in Romania (Gelmann et al, 2013), in New Hampshire USA (Fei et al, 2013), However, no significant association between urinary arsenic levels and SGA was reported in a study in Japan (Shirai et al, 2010). We found urinary arsenobetaine levels 42.25 mg As/L to be associated with an increased risk of SGA.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…16 Furthermore, the consequences of reduced infantile growth are far from negligible, because even a small reduction could affect health outcomes significantly in later life. 28 Previously, Afeiche et al 16 reported that prenatal lead exposure was associated with lower…”
Section: Discussionmentioning
confidence: 99%